Teachers' commitment focuses: a three-dimensioned view - Karakus, Mehmet; Aslan, Battal (Emerald Group Publishing Ltd, 2009)
Purpose - The purpose of this research is to determine high school teachers' organizational commitment levels, their commitment focuses and variables to which their commitments are related. Design/methodology/approach - A survey-based descriptive scanning model was used. The study was carried out in Elazig city on teachers working in public and private high schools. Taking in the whole population, the questionnaire was administered to 1,017 teachers. Findings - The results show that teachers' commitment focuses, their types and levels of commitment to these focuses vary according to their personal characteristics such as gender, marital status and tenure. Although female teachers are more affectively and normatively committed to the teaching profession than their male counterparts, they have low levels of normative commitment to the work group and low levels of continuance commitment (based on lack of investments) to the school in which they work. Married teachers are less affectively and normatively committed to the teaching profession than unmarried ones. However, married teachers' continuance commitment levels to the teaching profession and to the school in which they work are higher. As tenure increases, perceptions of investments having been made in schools increase and therefore teachers' continuance commitment levels to the focus of the school in which they work increase. Although one-to-five year tenured teachers have the highest levels of normative commitment to the teaching profession, they are the least affectively and normatively committed to the focus of work group. Research limitations/implications - The focus of the study is teachers working at high schools. Teachers working at various school levels may be committed to different focuses or to the same focus at different levels. It may be that a larger study across school levels would have revealed differences across them. Also, the underlying reasons why some teachers are committed to some focuses may be probed more profoundly. Practical implications - Keeping in mind the importance of teachers' commitment to various focuses and its effects on school effectiveness, educational leaders should take necessary measures to remedy the troubles which cause teachers' lack of commitment. In this context, school leaders may attempt to strengthen: female teachers' weak normative bonds to the work group, married teachers' weak affective and normative bonds to the teaching profession, and new teachers' weak affective and normative bonds to the work group. The findings reveal the need for more supportive and integrative managerial actions to raise teachers' levels of commitment. School leaders may be more concerning and develop special strategies contingent on their employees' personal characteristics to create high commitment workplaces. Originality/value - The relevant literature shows that the types and levels of teachers' commitment focuses are quite an under-researched area and the study has contributed to one's understanding of these issues.
Keywords: Job satisfaction; Teachers; Schools; Turkey